Towards a Theology of Holiness in the Laity: Newman, Escrivá and Wojtyła - Juan R. Vélez (Acta Universitatis Carolinae Theologica, 2023)
John Henry Newman, Josemaría Escrivá, and Karol Wojtyła are three modern saints who insisted on the general or universal call to holiness in everyday life, which until recent centuries focused on religious vows, degrees of prayer or mystical experiences. All three taught that this call is rooted in the sacrament of baptism with its subsequent growth by means of prayer, sacramental life, and the exercise of the virtues. They conceived of Christian holiness in terms of the imitation of Christ through the action of the Holy Spirit. For them, each Christian participates in the threefold office of Christ, Priest, Prophet, and King. Their teaching on divine filiation, sanctification of work and secular realities is a notable contribution towards a theology of holiness which calls for further elaboration.